Which and Whose Shari’a?: Historical and Political Perspectives on Legal Articulation of Islam in Indonesia - Arskal Salim (JURNAL INDO-ISLAMIKA, 2012)
Attempts at the implementation of shari’a in Indonesia have always been marked by a tension between political aspirations of the proponents and the opponents of shari’a and by resistance from the secular state. The tension had led to the profound and ongoing legal political dissonance in the formal application of shari’a rules in the country. A continuum between conflicts in meanings and direct contradictions in terms has resulted in a debate of which and whose shari’a to be implemented. This paper looks at the roots as well as the sources of those dissonances. It observes a number of conditions that make the articulation of religious law dissonant. It argues that more direct dissonance is discernible between the aspiration for the formal implementation of shari’a and constitutional rights of religious freedom. Arguing that despite shari’a has been able to seep into scattered legal aspects within Indonesian state and society and that the state has allowed shari’a to be incorporated in many ways into its legal system, nationally and regionally, it concludes that the state continues to control and restrict this dispersion and that shari’a remains tightly confined in Indonesia